(untitled) (Studia austriaca, 2024)
This article analyses the relation between Leo Perutz’s novel Zwischen neun und neun (1918) and the poetics and works of several German-speaking authors who can be considered Perutz’s literary role models. In chronological order, consideration will be given to the enigmatic, paradoxical situations characterising Heinrich von Kleist’s works, to E.T.A. Hoffmann’s serapiontisches Prinzip, irony and humour, and to Arthur Schnitzler’s narratological techniques and the resignation of his characters. The comparison with these models will demonstrate how the novel relates to the tradition of German literature, in what manner it surpasses it and which elements enable its correlation with modernism.